MISKONSEPSI UNSUR NOVELTY DALAM PENELITIAN PENDIDIKAN (TINJAUAN KAJIAN PENELITIAN RELEVAN PADA SKRIPSI MAHASISWA FTIK IAIN PONTIANAK) - Andina Nurul Wahidah (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Relevant research studies in a thesis should be able to describe elements of novelty, but the fact is that it is often only a list of relevant research. This misconception of novelty elements needs serious attention in the midst of rampant plagiarism. However, avoiding plagiarism does not necessarily indicate novelty in research. For this reason, this study aims to, (1) examine the novelty element based on the literature review stage, and (2) present recommendations for improvement of the misconceptions of the novelty element in the thesis. The quantitative approach in this study uses document observation as the main data collection. The population in this study were all FTIK IAIN Pontianak students who published theses for the year 2020-2021. Through random sampling technique, a sample of 40 thesis documents was obtained. The documentation technique with the student thesis document instrument was analyzed with descriptive statistics to see the average of each measured indicator. The results showed, (1) the novelty element based on the literature review stage in the thesis of FTIK IAIN Pontianak students only reached the first stage: compare (92.50%) and the second stage: contrast (85%). While the third stage: criticizing, the fourth stage: synthesize and the fifth stage: summarizes not presented with a percentage of 0%, and (2) recommendations for improvement of misconceptions about the novelty of the thesis, preferably in the sub-chapter of relevant research studies, preparation is made to find novelty by: create a novelty quadrant, and a cross check summarize table.